Social work fields of practice - Alston, Margaret; McCurdy, Samone; McKinnon, Jennifer 1959- (Oxford University Press, 2018)
Social work: fields of practice, third edition, takes the form of a conversation with students. Written by social-work experts, the book gradually uncovers many of the fields of practice a social worker is likely to encounter. Short, concise chapters allow students and lecturers a flexible approach to learning and teaching as they move through the book in an order that suits them. The book begins by examining groups social workers may work with across the various fields and then explains the fields of practice by drawing on the experience and practice wisdom of each chapter author. It covers the eight core fields of practice mandatory for students to achieve accreditation, before addressing new and emerging fields in social work. Social work: fields of practice provides an excellent grounding for social work students and ensures that they are well prepared for careers in the social work field."--